"THE ARCHAEOLOGY OF TANAMU 1 A Pre-Lapita to Post-Lapita Site from Caution Bay, South Coast of Mainland Papua New Guinea - David, Bruno (Archaeopress Publishing, 2022)
Presenting results from Tanamu 1, the first site to be published in detail in the Caution Bay Studies in Archaeology series. Yielding well-provenanced and finely dated assemblages of ceramics, faunal remains, and stone and shell artefacts, these remarkable sites extend the range of the Lapita cultural complex to the south coast of Papua New Guinea.